Impact of blue light exposition to alertness of shift workers, patients with sleep deprivation, Alzheimer’s disease, or post-traumatic stress disorder - Żołnierek, Maja; Siekierko, Nikola; Lubczyńska, Zuzanna; Świętochowski, Jakub; Lewandowski, Mateusz; Kotusiewicz, Wiktoria; Popravko, Yevheniia; Bienia, Grzegorz (Journal of Education, Health and Sport, 2023)
Introduction and purpose: In certain professions it is necessary to work at night and to maintain alertness and concentration at that time. Additionally in some conditions such as Alzheimer’s disease and post-traumatic stress disorder sleep deprivation is both a symptom and an aggravating factor. A non-pharmacological method is needed to impact the maintenance of concentration and to help the workers adapt to shift work as well as improve their sleep quality. The purpose of this paper is to present recent scientific findings on the effects of blue light on improving concentration and attentiveness in shift workers and people suffering from sleep disorders, Alzheimer's disease, or post-traumatic stress disorder. A brief description of the state of knowledge: Circadian rhythm is a mechanism, which regulates daily functioning of humans and a variety of other species. Light exposure, especially to blue light, is the most crucial factor disrupting circadian consistency. The relationship between the time maladjustment, biological rhythms and factors from the outside world is called phase angle of entrainment. Summary: Studies conducted on various groups have shown the effectiveness of modified light interventions on concentration and focus during shift work at night. Exposure to blue light appears to be a safe method that can improve work quality, concentration and focus in people who work at night. Exposure to light brings hope for improving the quality of life of people with Alzheimer's disease and maintaining their independence longer, which can ease the burden on their caregivers. Establishing some routine in the form of blue light exposure in people with post-traumatic stress disorder also appears to be an easy and accessible method for reducing the severity of PTSD symptoms, especially sleep disturbances.